A WAVELET OPERATIONAL MATRIX METHOD FOR SOLVING INITIAL - BOUNDARY VALUE PROBLEMS FOR FRACTIONAL PARTIAL DIFFERENTIAL EQUATIONS. (2016) - CHANDEL, RAGHVENDRA SINGH; SINGH, AMARDEEP; CHOUHAN, DEVENDRA
No abstract available